Identifying Factors Influencing the Adoption of CIFRS/CIFRS for SMEs in Cambodia - Hin, Kosla; Lim, Siphat (International Review of Management and Marketing, 2024)
The data collected from the survey in this study revealed that a total of 2431 firms successfully filled out and returned the questionnaire. Among these, 73.79% were categorized as non-adopters of CIFRS, whereas 26.21% were recognized as adopters of CIFRS. The findings derived from the logistic regression model indicated that the latent variables, including financial reporting components, stakeholder knowledge and attitudes, the internal control system, and the costs related to the implementation of CIFRS, exerted a highly positive and statistically significant impact on the probability of adopting CIFRS in Cambodia at the 1% significance level. However, the variable concerning financial reporting components demonstrated significance only at the 5% level. It is important to mention that the estimated latent variables were determined using explanatory factor analysis (EFA). The estimated coefficients for the control variables were 0.997 for number of employees, 1.243 for assets, 5.581 for filing financial reports with ACAR, -0.725 for ACAR's enforcement of laws related to CIFRS implementation, and -0.644 for inconsistencies in financial information provided by CIFRS compared to standards set by the General Department of Taxation. Each parameter associated with the control variables had statistical significance at the 1% level.